Rediscovery of Croton hadrianii (Euphorbiaceae), a well distributed but long-forgotten species in Brazilian Amazon - Sodré, Rodolfo Carneiro; Da Silva, Marcos José (Phytotaxa, 2018)
During a taxonomic study on Croton sect. Geiseleria from Brazil, 40 specimens were found from the southern portion of the Brazilian Amazon that correspond to C. hadrianii, a species hitherto known only from its original description and with the type locality within Brazil unknown. We present an amended description of C. hadrianii providing the first information on fully developed fruits and seeds, which previously undocumented, morphological characterization, as well as comments on its geographical range, including a distribution map, conservation status, and period of flowering and fruiting. The species is also illustrated and photographs in its habitat for the first time. Typification is also presented and the species systematic position within Croton sect. Geiseleria is discussed. Additionally, we provide a key to the 16 species of Croton sect. Geiseleria occurring in the Brazilian Amazon, as well as field images for most of them.